Cerebrovascular Diseases Elucidating Key Principles - Bozzetto Ambrosi, Patricia (IntechOpen, 2022)
This book elucidates the key principles of cerebrovascular diseases (CVDs) in three sections. The first section addresses relevant pathophysiological aspects, diagnosis, treatment, and complications of CVDs, the second section examines CVDs in resource-poor settings and the geriatric population, and the final section discusses atrial fibrillation and cryptogenic stroke.